DEVELOPING A NEUROSAINS-BASED ARABIC CURRICULUM - Nada Nabilah Syafiqoh; Yuli Imawan; Okitra Asri Nurazim; Putri Nurinadia (STIQ Amuntai, 2023)
The purpose of this article is to discuss the role of Neurosains in the modernization of the Arabic curriculum, including its strategic and practical reconstruction. One is the emergence of international integration, brain-based learning, and character development based on neuroscience or neuroscience approaches. The basic principle of this study is the correct brain functional statement as the foundation of Arabic curriculum development. This paper aims to demonstrate how the Arabic learning process can be integrated with neuroscience approaches by optimizing right and left brain functions. This type of research is a literature study with Content Analysis (Analysis content) in the form of descriptive analysis. The research method uses primary sources from previous articles and books. The results showed that the application of neurosains can be implemented into the formulation of Arabic curriculum development with Circuit; 1) optimization of the right and left brain nervous system; and 2) optimization of the nervous system of the right and left brain. 2) incorporate the role of the brain into the Educational Foundation and the psychological aspects of cognitive (the substance of Arabic), psychomotor (mastery of Arabic skills), and affective (attitudes, values, and character) into Arabic learning design; and 3) link these three aspects into the nature of Arabic learning objectives, methods, strategies, and techniques. On that basis, neuroscience can be incorporated into modern-era Arabic learning curriculum development standards.